Website characteristics that influence consumers’ online purchase intention within the fast-food industry - Pillay, Gabrielle (My University, 2022)
The fundamental goal and purpose of this study is to examine the website characteristics that influence consumers’ online purchase intention within the fast food industry. While reviewing prior literature, it was indicated that investigations around website characteristics focused mainly on the banking sector and commercial industries. This study contributes to literature by focusing on the fast food industry. This study examined the following website characteristics: perceived ease of use, perceived usefulness, trust, security, visual and audio elements, interaction and involvement, time-saving orientation, website quality, relative advantage, and service factors. The results indicated that (a) perceived ease of use, perceived usefulness, security, time-saving orientation, and relative advantage had a positive relationship with online purchase intention; (b) interaction and involvement, website quality, and service factors had a significant relationship with online purchase intention within the fast food industry. This study has applied a quantitative approach to investigate the website characteristics that influence consumers’ online purchase intention of fast food. The study used a 5-point Likert Scale adapting questions from previous literature. The researcher collected a total of 204 responses, however, only 202 responses were viable. These responses were collected through an online survey due to COVID-19. This current academic study intended to develop and contribute to literature regarding the website characteristics that influence online purchase intention of fast food as well as extend the applicability of the Technology Acceptance Model and Theory of Flow to the fast food industry. This study also intended to inform and assist marketing managers within the fast-food industry by providing them with research and evidence regarding the website characteristics which motivate consumers’ online purchase intention of fast food.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Fast food industry; Online purchase; Website characteristics